The Role of ANC, Posyandu, and Immunization Visits in Preventing Stunting in Toddlers: A Case Study in West Sumba District - Bata, Verayanti Albertina (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Stunting in children under five is a serious global health problem, including in West Sumba Regency, Indonesia. Data from the West Sumba District Health Office shows that out of 100 toddlers, 12 are underweight, 30 are stunted, and 5 are obese. The stunting rate in West Sumba in 2018 also increased compared to 2016 and 2017, from 29.6% to 36.4% or 364 cases.Data from the West Sumba District Health Office shows that the second highest number of stunted infants is at the Puuweri Community Health Center . This study aims to identify the relationship between ANC visits, Posyandu, and immunization with the incidence of stunting in toddlers in West Sumba Regency. This study used an analytical observational research design with a cross- sectional study type. Data were obtained through interviews with pregnant women and parents of children under five who actively participated in ANC visits, Posyandu, and immunization in the region. The calculation results show that the required sample size is 88. Data analysis involved a chi-square test to identify the relationship between ANC, Posyandu, and immunization visit variables and stunting incidence. The results showed that there was a significant relationship between ANC visits (p = 0.000), Posyandu (p = 0.000), and immunization (p = 0.000) with the incidence of stunting in toddlers in West Sumba Regency. Participation in ANC, Posyandu, and immunization visits plays an important role in reducing the risk of stunting in toddlers in West Sumba Regency.